2011
DOI: 10.1016/j.bbamcr.2011.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of 1α,25-dihydroxyvitamin D3-dependent repression of interleukin-12B

Abstract: Interleukin 12 (IL-12) is a heterodimeric, pro-inflammatory cytokine that plays a central role in activation and differentiation of CD4(+) T cells into interferon-γ secreting T-helper type 1 cells. IL-12B, a gene encoding the larger subunit of active IL-12, has been reported to be down-regulated by the nuclear hormone 1α,25-dihydroxyvitamin D(3) (1α,25(OH)(2)D(3)), but the mechanism of the regulation is unknown. In this study, we have examined the molecular mechanism of transcriptional regulation of the IL-12B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 39 publications
2
30
0
Order By: Relevance
“…(55) Finally, IL-12, a proinflammatory cytokine that plays a central role in activation and differentiation of CD4(þ) T cells into interferon-g secreting T-helper type 1 cells, has been reported to be downregulated by 1,25-dihydroxyvitamin D treatment. (55,56) In our study, all tested markers of innate immunity showed some response to both types of vitamin D, but it was significantly more pronounced with HyD for four markers of innate immunity (eotaxin, IL-12, MCP-1, and MIP-1b). The response to both types of vitamin D was very rapid in the first 5 days after treatment initiation, during which all but IP-10 and RANTES decreased, followed by an increase of all markers during a 2-day period between day 6 and 8, and a further decline thereafter.…”
Section: Discussionmentioning
confidence: 45%
“…(55) Finally, IL-12, a proinflammatory cytokine that plays a central role in activation and differentiation of CD4(þ) T cells into interferon-g secreting T-helper type 1 cells, has been reported to be downregulated by 1,25-dihydroxyvitamin D treatment. (55,56) In our study, all tested markers of innate immunity showed some response to both types of vitamin D, but it was significantly more pronounced with HyD for four markers of innate immunity (eotaxin, IL-12, MCP-1, and MIP-1b). The response to both types of vitamin D was very rapid in the first 5 days after treatment initiation, during which all but IP-10 and RANTES decreased, followed by an increase of all markers during a 2-day period between day 6 and 8, and a further decline thereafter.…”
Section: Discussionmentioning
confidence: 45%
“…An earlier report attributed the down-regulation of IL-12 via interference of 1α,25(OH) 2 D 3 /VDR with NF-κB binding to proximal IL-12 promoter regions (D'Ambrosio et al, 1998). It has been suggested in the more recent report that this suppression of proximal sites is due to epigenetic changes at that location via the distal VDRE binding sites identified in the more recent study (Gynther et al, 2011) (Figure 3). …”
Section: α25(oh)2d3 As Regulator Of Cytokine Gene Expression Protementioning
confidence: 75%
“…IL-12B has been identified as a 1α,25(OH) 2 D 3 -dependently down-regulated gene in LPS-treated THP-1 cells. The gene harbors two VDR binding sites within ~6 kb upstream of the transcription start site to which the VDR and its partner retinoid receptor (RXR) recruit co-repressors and consequently induce epigenetic changes associated with gene repression (Matilainen et al, 2010b; Gynther et al, 2011). An earlier report attributed the down-regulation of IL-12 via interference of 1α,25(OH) 2 D 3 /VDR with NF-κB binding to proximal IL-12 promoter regions (D'Ambrosio et al, 1998).…”
Section: α25(oh)2d3 As Regulator Of Cytokine Gene Expression Protementioning
confidence: 99%
“…For example, 1α,25(OH) 2 D 3 enhances the differentiation of monocytes into functional macrophages with increased phagocytic capacity and altered cytokine-secreting capacity, but impairs the differentiation of monocytes into dendritic cells [100]. The main 1α,25(OH) 2 D 3 targets in differentiating monocytes are anti-microbial peptides, such as cathelicidin, co-stimulatory molecules, such as CD14 [35], and cytokines, such as interleukins 10 and 12b [101,102]. The new insight of the dominant role of VDR in the granulocyte/monocyte module now allows more specific investigations on the functional interplay of VDR with its partner transcription factors, for example with the pioneer factors CEBPA and SPI1.…”
Section: Perspective 6: Vdr As a Module Componentmentioning
confidence: 99%